2009
DOI: 10.1080/14780880701734545
|View full text |Cite
|
Sign up to set email alerts
|

Q Methodology and a Delphi Poll: A Useful Approach to Researching a Narrative Approach to Therapy

Abstract: were used to extract eight accounts of narrative therapy, five of which are qualitatively analysed in this paper. Agreement and differences were identified across a range of issues including the social construction of narratives, privileging a political stance or narrative techniques and the relationship with other therapies, specifically systemic psychotherapy. Q methodology, combined with the Delphi poll was a unique and innovative feature of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The two sets of data were then compared, to see whether there was consensus. As TA is helpful to cast light upon individual responses and attempt to make sense of them in context (Braun and Clarke, 2012), and a Delphi poll facilitates consensus amongst a group of knowledgeable clinicians (Wallis et al, 2009), the combination of these two methodologies was intended to allow synthesis. This offers a more integrated perspective between individuals and 'experts'.…”
Section: Design: Overviewmentioning
confidence: 99%
“…The two sets of data were then compared, to see whether there was consensus. As TA is helpful to cast light upon individual responses and attempt to make sense of them in context (Braun and Clarke, 2012), and a Delphi poll facilitates consensus amongst a group of knowledgeable clinicians (Wallis et al, 2009), the combination of these two methodologies was intended to allow synthesis. This offers a more integrated perspective between individuals and 'experts'.…”
Section: Design: Overviewmentioning
confidence: 99%
“…Q methodology was first developed by Stephenson (1935) and has been widely described as: a conceptual framework and analytical procedure for the exploration of subjectivity; as a means for studying subjective or contestable issues; and as a tool for examining social problems and related solutions (Brown 1980;Capdevila 1999;Curt 1994;Kitzinger 1987;Lazard 2009;Senn 1996;Stainton Rogers 1991;Wallis, Burns & Capdevila 2009). …”
Section: Contextualising Qmentioning
confidence: 99%
“…From the answers to these questions, statements about narrative therapy were generated, and a wider group of practitioners were asked to perform a Q-sort (Watts & Stenner, 2005). As the combination of a Delphi Poll and Q-sort was a unique feature of this research, this methodology is reported in fuller detail in a different paper (Wallis, Burns, & Capdevila, 2009). In this paper, we will concern ourselves more with the theoretical, clinical and research implications of the fi ndings.…”
Section: Introductionmentioning
confidence: 98%